SOCIO-ECONOMIC STATUS IN RELATION TO LEARNING PROBLEMS OF STUDENTS. - Roberts, Susan C. (Education)
Thirty children in a special public school for the emotionally disturbed in Florida were administered individualized instruments in order to measure their intelligence, achievement, language ability, and behavior patterns. The socioeconomic status of the children's families was determined using the revised occupational measure of the Warner Scale. Whereas no significant relationships were obtained between socioeconomic status and the educationally relevant variables, several highly significant relationships were found between the educationally relevant variables to one another. An additional number of noteworthy relationships observed between the variables have implications for teachers with regard to anticipating their children's needs and planned sequential remedial academic and social programs for them on a day-to-day basis.